THE NATIONAL APPLICATION OF FOREIGN LAW - Berrabah Mounir; Touirat Abderrahmane (International Journal of Innovative Technologies in Social Science, 2026)
When a dispute is brought before a judge which is related to a legal relation in the field of private law, and includes a foreign element, the judge looks for the most appropriate law to govern the dispute. In this area, the legislator gives the judge, as an exception, the possibility to apply a foreign law instead of his own law, when the rules of reference (conflict rules) established by the legislator direct him to that. Here, a jurisprudential theory appeared, trying to put a legal basis upon which it is possible to rely when the national judge applies the foreign law.